(untitled) (Global Journal of Human-Social Science, 2012)
The paper analyses Spatial nature of activities of the people in Ilorin especially the length of time spent on each activity. Data were collected from 500 residents of Ilorin, each of whom completed a time budget diary over one week. Descriptive statistics wereused to summarize the data while stepwise regression analysis was used to determine the factors responsible for the spatial fixity of respondents’ activities. The result shows that the activities were fixed in time and three variables: age, income and occupation were the major determinants of the time spent on the activities. The study also shows clearly that the temporal structure of activity in Ilorin is different from what obtains in Western cities where there is flexibility in the usage of time.